Outpatient Service Business Development in an Effort to Reduce Service Time - Nila Novita; Alita Dewi Percunda; Djazuly Chalidyanto (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Hospital service quality should be developed based on customer needs and satisfaction. Long service time at Bhayangkara Kediri Hospital Outpatient Unit (267,62 Â± 136,41 min) becomes a problem for management. The process is an asset for an organization, especially the core process should be well managed. Business process management has been viewed as an effective concept to improve processes continuously. It is an operational research combining document review, stakeholder interview, focused group discussion, quantitative and qualitative process analyze, prioritization, and root cause analysis to give process redesign recommendations. There are five core processes in the outpatient unit, and we focus our research on the dispensing process in pharmacy. Then we made a process model based on evidence and interview-based discovery. The cycle time efficiency of the prescription analysis process was the worst with a value of 0.31. With non-value activities reach to 40% of all activities with the waste are over processing, waiting, and transportation. The selected problem was the disposition of prescriptions to the dispensing unit as waste. Based on the root cause analysis, we suggest two recommendations. For the short-term redesign, we support the use of a basket to transport the prescription embedded in the operational procedures. And for the long-term redesign, we suggest the implementation of electronic prescribing. These redesigns are assumed to reduce waiting time by 2.5 â€“ 16.2 % of service time.Â